2012
DOI: 10.1186/1743-422x-9-162
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of HDV isolates from HBsAg positive patients in Karachi, Pakistan

Abstract: BackgroundIn spite of a high occurrence of Hepatitis Delta in the province of Sindh in Pakistan, no genetic study of Hepatitis Delta virus (HDV) isolates from this region was carried out. The aim of this study is to analyze the genetic proximity within local HDV strains, and relationship with other clades of HDV, using phylogenetic analysis.ResultsPhylogenetic analysis of nucleotide sequences of the Hepatitis Delta Antigen (HDAg) R0 region obtained in this study, showed considerable diversity among the local s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…As glycine and lysine have similar characteristics as serine and arginine, and besides the lower importance of serine 2 compared with serine 177 and the ability of methyltransferase to recognize lysine as a substrate [2,55,56], these substitutions may not hinder HDAg function. The other amino acid substitutions, including those in positions 198 and 202, are similar to already reported residues from other countries; the possible functional effect on HDAg properties requires further analyses [8,11,19,20].…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…As glycine and lysine have similar characteristics as serine and arginine, and besides the lower importance of serine 2 compared with serine 177 and the ability of methyltransferase to recognize lysine as a substrate [2,55,56], these substitutions may not hinder HDAg function. The other amino acid substitutions, including those in positions 198 and 202, are similar to already reported residues from other countries; the possible functional effect on HDAg properties requires further analyses [8,11,19,20].…”
Section: Discussionsupporting
confidence: 73%
“…These isolates had a close relation to African strains, and phylogenetic tree topology indicated that these strains (D32, D33 and D34) might be the basal lineage that diverged earlier from the other Iranian HDV genotype 1. Although people in this region of the country are considered in close relationship with their relatives from Afghanistan and Pakistan, phylogenetic trees constructed by the C-terminal of L-HDAg, either from nucleotides or amino acids, did not cluster these sequences together with reported HDV genotype 1 isolates from Pakistan [19] nor from Afghanistan (data not shown) [16]. This discrepancy may be explained by the use of a very small portion of HDV genome for evolutionary analysis in these studies.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations